Interactive training for active support: perspectives from staff. - Totsika V; Toogood S; Hastings RP; Nash S (Journal of Intellectual & Developmental Disability, 2008)
Background In this study, we describe the experience of participating in interactive training (IT) for active support (AS). Staff (N = 58) working with adults with an intellectual disability (ID) received IT on providing effective assistance for participation in daily activities. Method Semi-structured interviews were conducted with staff (N = 37) on their experience of IT, the way it affected their work, and their views on the implementation of AS. Results High levels of satisfaction with IT were reported. Most staff identified at least one skill learnt during IT that they were still using 8 months later. No clear and consistent picture of AS implementation emerged across the service; staff identified a number of barriers, with lack of managerial support as the most significant. Conclusions Interactive training can directly affect staff behaviour and has the advantage of being positively perceived by staff. However IT alone cannot ensure successful AS implementation, which is affected by a number of other factors, such as managerial support and input, residents' challenging behaviours, and staffing levels.